Pemberdayaan “Perempuan Ladang” melalui Pemanfaatan Fintech dan Komersialisasi untuk Meningkatkan Income PHKom Perempuan Aman Menteng - Yusnaini, Yusnaini; Fitri Handayani; Hendy, Hendy (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Women of the Field, specifically the women of PHKom Perempuan AMAN Menteng, have limited knowledge about Fintech and the overall marketing stages of products. Partners also lack knowledge about the importance of intellectual property rights for a product's brand. The aim of this community service activity is to assist partners in enhancing their knowledge in accounting, specifically on the use of fintech such as E-Wallets (OVO and Dana) and QRIS for digital payments. In marketing, it involves applying marketing strategies to products, starting from packing, branding, and promotion, and helping partners register their brand's intellectual property rights. This activity was conducted with the women of PHKom Perempuan Aman Menteng, in Amplas Village, Deli Serdang Regency, about 8 km from STMB MULTISMART. The location was chosen because the village has a community of women who own fields and home-based businesses as their main source of income. The results of this community service are that the partners are now able to use digital wallets like OVO and Dana, and QRIS for cashless transactions. Additionally, in terms of marketing, partners have more modern production and packing tools, which have improved productivity, and their product brand is now registered with intellectual property rights. The result of the activity implementation is that the partner has become more productive in producing products due to the availability of production support equipment, which has led to an increase in the partner's income.